A CRITICAL ANALYSIS OF GENDERED DISCOURSE PATTERNS IN THOMAS HARDY’S NOVEL TESS OF THE D’URBERVILLES - Aiman Imran; Yusra Ali; Savaira Muzammil; Lalarukh Durrani; Mahnoor Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
The study examines Thomas Hardy’s work Tess of the d’Urbervilles in relation to Deborah Tannen’s Genderlect Theory, focusing on the differing linguistic styles of men and women. The main character, Tess Durbeyfield, is a young woman who lives in the country. Her life is marked by sorrowful experiences and challenges. The narrative unfolds when Tess’s family learns about their aristocratic heritage. This leads Tess to the d’Urberville family, which begins a series of painful events. Tess is assaulted by Alec d’Urberville, faces rejection from society, and goes through more pain when her husband, Angel Clare, leaves her after finding out about her past. The way the novel shows Tess’s challenges gives us important insight into how men and women interacted in the Victorian era. For women, being beautiful and innocent could be both good and bad. The paper looks at how men and women use language differently. It shows that these ways of talking relate to the larger roles of men and women and their power in Victorian society. Using Tannen’s Genderlect Theory, the study looks at how men and women communicate differently. Men often use "report talk" to show they are in charge, while women prefer "rapport talk" to make connections. This comparison highlights how women were treated unfairly in Victorian society and shows how language helps maintain social rankings. Hardy shows how Tess’s language changes from innocent to strong, reflecting her fight against unfair social rules. The study helps improve our understanding of how men and women communicate in writing, which is important for both literary analysis and the study of language in society. It also highlights how language shapes and questions gender roles, making discussions about language, gender, and power in literature more interesting and important.